Internalization of Islamic Educational Values through the Merariq - Mukminah Mukminah; Hirlan Hirlan (Newinera Publisher, 2026)
The marriage tradition of the Sasak Merariq is ideally a vehicle for Islamic character education, based on the philosophy of